Rendimiento Diagnóstico de la Prueba Molecular Rápida GeneXpert MTB/RIF en Comparación con la Baciloscopía para el Diagnóstico de Tuberculosis Pulmonar en Pacientes Adultos Peruanos - Rodriguez- Saldaña , Christian Alberto (2026)
Introduction: GeneXpert is a revolutionary tool for tuberculosis (TB) detection, with its main advantage being its speed and accuracy in identifying the pathogen and detecting rifampicin resistance within hours. Objective: To determine the diagnostic performance of GeneXpert MTB/RIF compared with bacilloscopy for the diagnosis of pulmonary tuberculosis in adult Peruvian patients. Methods: A cross-sectional analytical study was conducted based on a review of secondary databases. The study population included patients treated at a hospital in northern Peru between 2019 and 2022 who underwent diagnostic tests for tuberculosis, such as bacilloscopy, GeneXpert, and culture. Patients with incomplete records and those with results reported as errors were excluded. Results: A total of 800 out of 1,044 samples were selected for tuberculosis diagnosis, of which 75.3% (n = 601) were positive. The median age was 43 years; 66.5% (n = 532) were men, and 22.3% (n = 178) were older adults. Culture for acid-fast bacilli (AFB) was positive in 89.5% (n = 538) of the 601 samples, while GeneXpert detected tuberculosis in 73.5% (n = 585) and bacilloscopy in 58.4% (n = 466) of 798 samples. GeneXpert showed higher sensitivity than bacilloscopy (97.9% vs. 77.4%), with almost perfect agreement with culture (kappa index = 0.847). Conclusion: These findings highlight the importance of considering GeneXpert as an effective diagnostic tool for pulmonary tuberculosis in similar settings